তরু নীড় - এস ও এস শিশু পল্লী SOS SHISHU POLLI, BARISHAL - Momo, Mumtahinah (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2022.